KEDUDUKAN HUKUM PRIA DALAM MENGAKSES SISTEM ELEKTRONIK DI LAPTOP YANG DIIZINKAN TEMAN PEREMPUANNYA (Legal status of men accessing electronic systems on laptop which are permitted by Female Friend) - Parlindungan Satria (Problematika Hukum, 2019)
Information Technology, media and communication role has changed society and human civilization behaviour globally. Information and communication technology development is very quick and world relations are borderless, further significant social, economic and cultural changes are quickly. The impact of information technology contributes to welfare, progress and society civilization as well as acts against the law.The man and his girlfriend used information and communication technology facilities in which the man lend her a "Laptop" then they agreed to use the same "password" to use the laptop.Man was reported by his girlfriend on act the accusation that the man had accessed the laptop even though he has the girlfriend’s permission which laptop position was being "logged in".When the man opened "Facebook", there was a "chat" between his girlfriend and another man tell about the sexual nature of the accused man. There was disharmony. A man changed his girlfriend's Gmail, Facebook, yahoo passwords, and posted WhatsApp conversations between his girlfriend and another man on his girlfriend's Facebook.This research is related to illegal access through a district court decision for man, Number: 414/Pid.B/2021/PN.Jkt.Pst. decided on article 30 paragraph 2, Law of the Republic of Indonesia No. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Technology (ITE) for the man.The objective research is to provide legal certainty for man that the article is not in accordance with legal certainty, because the man has obtained permission from his girlfriend, not the article changing his girlfriend's password.The method is normative legal research and statute approach which will discuss these allegations with secondary data then the research result can provide legal certainty and justice by changing the multiple interpretations of the article accusing the man that the legal position of man is not doing illegal access because he got girlfriend’s permission.